SMARANDACHE Pi B-1 CURVES OF BIHARMONIC NEW TYPE CONSTANT Pi(2) - SLOPE CURVES ACCORDING TO TYPE-2 BISHOP FRAME IN THE SOL SPACE - Körpınar, Zeliha; Körpınar, Talat (Editura Bibliotheca-Bibliotheca Publ House, 2021)
In this paper, we study Smarandache Pi B-1 curves of biharmonic new type constant Pi(2) - slope curves according to type-2 Bishop frame in the Sol space. Type-2 Bishop equations of Smarandache Pi B-1 curves are obtained in terms of base curve's type-2 Bishop invariants. Subsequently, we express some interesting relations.
Keywords: Type-2 Bishop frame; Sol space; Smarandache Pi B-1 curve; Electromagnetic-Field Vectors; Coiled Optical-Fiber; Soliton Propagation; Inextensible Flows; Energy; Particles; Version